Evaluation of the impact of urban water systems on railways: The scenario of track flooding caused by a water main burst. (March 2020) - Faramehr, Samane; Hemida, Hassan; Fujiyama, Taku
Failures and disruption scenarios can reveal inherent but little known dependencies that exist between technical infrastructure systems. Whereas the dependencies between infrastructures in their normal state of operation are usually obvious and mutually correlated, interdependencies, when systems are disrupted, show a great deal of variety, depending on the specific scenario. The literature reveals the lack of a proper tool that can evaluate and quantify the scenario of track flooding caused by a water main burst, a cross-sectoral failure that can impact the operation of two urban infrastructure systems: the railways and the water supply. This work presents an approach to investigate the impact of urban water systems on railways and applies it to the case study of the Thameslink railway and Thames Water assets in London. The developed tool can be integrated into city level water supply GIS systems to facilitate the understanding of external risks (transport disruption) caused by an internal failure (water main bursts). Also, the results can help railway system operators facilitate the decision-making process in terms of drainage policy and maintenance activities.